Efek Radiasi terhadap Perubahan Jumlah Leukosit dan Eritrosit pada Pasien Kanker Payudara Sebelum dan Setelah Radioterapi - Agustina Dwi Prastanti; Sri Wahyuni; Siti Masrochah (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Breast cancer is second cancer after a lung cancer as a cause of death from cancer in women. Breast cancer patients underwent radiotherapy using Co-60 with a total dose of 50 Gy and fractionated doses 2 Gy/day. Ionizing radiation takes a bad affect blood cells (leucocytes and erythrocytes). The purpose of this research to find out the changing in the number of leukocytes and erythrocytes in breast cancer patients who underwent radiotherapy.Methods: The research uses the quantitative method with survey approach. Samples size in this research is 30 women who had breast cancer stage III. The independent variable of this research is radiotherapy treatment with  Co-60, with 50 Gy total dose and fractionated dose about 2 Gy with 5 times in one week. The dependent variable in this research is the changing in the number of leucocytes and erythrocytes before irradiation, after 5 times irradiation and after 10 times irradiation. Data analyze used statistical with a comparative method to take a result.Results: The results have found the average number of leucocytes in breast cancer patients before radiotherapy ±6,41 thousand/µL after the irradiation  5 times decrease to ±5,38 thousand/µL and after the irradiation, 10 times decrease to ±4,50 thousand/µL. The average number of erythrocytes in breast cancer patients before radiotherapy ±4,50 million/µL, after the irradiation 5 times decrease to ±4,17 million/µL and after the irradiation 10 times to decrease to ±3.90 million/µL. Based on the statistical test, the results have found significant value 0,000 0.05, then Ha is accepted. It means there are changes in the number of leucocytes and erythrocytes in breast cancer patients before and after radiotherapy.Conclusion: Leukocyte levels change is a decline of 1:03 thousand / mL or at 16:07%. Whereas after irradiation with 5 times to 10 times after irradiation decreased by 0.88 thousand / mL or 16:36%. Erythrocyte levels change is a decline of 0:33 million / mL or at 7:33%. Whereas after irradiation with 5 times to 10 times after irradiation decreased by 0:27 million / mL or 5:04%